Activities of the Council of Europe in ensuring the human right to information: issues of compliance with the modern challenges of democracy - Danylenko, Serhii; Shustenko, Sofiia (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2020)
In the article, the authors review and systematize the activities of the Council of Europe in ensuring one of the key factors of liberal democracy – freedom of expression, which is a prerequisite for the implementation of a number of other rights and freedoms. The authors categorize the basic documents, both those that have already become classics and those adopted recently, where this phenomenon has found legal consolidation. It studies the way in which it affects the formation and development of the human right to information in Europe. Attention is drawn to the fact that, with the emergence of new ways of disseminating information, including the potential of the internet first and foremost, the accumulation of information and the European community’s efforts to protect this fundamental democratic right, its further strengthening remains urgent. The Council of Europe has lost control over the observance of the human right to information, and information is used with destructive intent, which poses a danger to one of the fundamental values on the basis of which European society operates today, and raises the risk of the restoration of authoritarianism. First and foremost, there is a threat of authoritarianism in the new democracies of Eastern Europe. The global COVID-19 pandemic and the recession of the world economy, which encourages citizens to choose authoritarian leaders, may be the trigger for slipping into authoritarianism.

Autorzy artykułu dokonują przeglądu i systematyzacji działań Rady Europy w zapewnianiu jednego z kluczowych czynników demokracji liberalnej – wolności słowa, która jest warunkiem realizacji szeregu innych praw i wolności. Autorzy kategoryzują podstawowe dokumenty, zarówno te, które już stały się klasyką, jak i te przyjęte niedawno, w których zjawisko to uległo utrwaleniu prawnemu. W artykule zbadano, w jaki sposób wpływa ono na kształtowanie i rozwój prawa człowieka do informacji w Europie. Zwraca się uwagę na fakt, że wraz z pojawieniem się nowych sposobów rozpowszechniania informacji, w tym przede wszystkim wobec potencjału internetu, oraz gromadzeniem informacji i wysiłkami społeczeństw Europejskiej na rzecz ochrony tego podstawowego w demokracji prawa, jego dalsze wzmacnianie pozostaje istotną kwestią. Rada Europy utraciła kontrolę nad przestrzeganiem prawa człowieka do informacji, a informacje są wykorzystywane w destrukcyjnych celach, co stanowi zagrożenie dla jednej z fundamentalnych wartości, na podstawie których funkcjonuje dziś społeczeństwo europejskie zwiększając ryzyko przywrócenia autorytaryzmu. Autorytaryzmem zagrożone są przede wszystkim nowe demokracje Europy Wschodniej. Światowa pandemia COVID-19 i światowa recesja gospodarcza, w wyniku której obywatele chętniej wybierają autorytarnych przywódców, może być przyczyną wprowadzenia autorytaryzmu.
Działania Rady Europy w zakresie zapewniania prawa człowieka do informacji: kwestie zgodności ze współczesnymi wyzwaniami demokracji
Keywords: Council of Europe; human right to information; media; stereotypes; disinformation; content control; access to information; Rada Europy; prawo człowieka do informacji; media; stereotypy; dezinformacja; kontrola treści; dostęp do informacji